Pengembangan Aplikasi Android Rekomendasi Lapangan Badminton di Kota Malang dengan Group Decision Support System (GDSS) dan Location Based Service (LBS) - Chrysler Imanuel; Ratih Kartika Dewi; Muhammad Aminul Akbar (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Badminton is one of the most famous sports in Indonesia. Badminton is a type of sport that is played by hitting a shuttlecock using a racket until it goes beyond a jarring or net that is stretched in the middle of the field. When choosing a badminton court to rent it is usually done with a group people playing. Therefore, this study aims to develop a badminton court recommendation application in Malang city by using a Group Decision Support System (GDSS) that can provide recommendations for a group of users. This application was built for the Android operating system. To get the results of group recommendations the TOPSIS and Borda algorithms are used. The application will display a list of badminton fields in Malang along with detailed information and location of the field. The application also applies the Location Based Service (LBS) method, which is marked by the availability of directions feature, so users can easily search for the route to the desired badminton field using the help of the Google Maps application. There are 3 criteria used in the application, namely price, distance and number of fields. Testing the functional requirements with the blackbox method obtained 100% results. The results of testing the comparison of system output with manual calculations obtained 100% valid results. Usability testing using SUS obtained an average value of 80 with Grade Scale getting a B value and Adjective Rating getting a Good value.